Modelling the propagation of magnetic fields from multiple diverse sources - Glyva, Valentyn; Murr, Pierre; Biruk, Yana; Dolia, Olena; Levkivskyi, Ruslan (Національний технічний університет "Харківський політехнічний інститут", 2025)
Man-made magnetic fields have a negative impact on humans. When there are many sources of magnetic fields, their combined effects are unpredictable. The patterns of propagation of fields from different sources vary. This complicates the process of planning the placement of electrical equipment in specific areas. The most acceptable way to predict the electromagnetic environment at the design stages is to model the propagation of magnetic fields from multiple sources. The aim of the study is to model the propagation of magnetic fields from multiple sources with different patterns of spatial propagation. Research results. The most significant factor of constant influence on humans is extremely low frequency electromagnetic fields. At the same time, the magnetic component of these fields is not shielded by equipment housings. Therefore, it is advisable to model the propagation of the magnetic field. It is shown that all sources of the magnetic field can be considered as a combination of magnetic dipoles. To model the propagation of a dipole-type magnetic field, the ratio for the vector magnetic potential is used. To model the propagation of dipole-quadrupole-type magnetic fields, it is advisable to use Gauss's equation for the scalar potential. This allows the presence of spatial harmonics of the magnetic field to be taken into account. The propagation of the magnetic field in the plane where people are located was modelled. It has been established that even in the presence of field superposition, the change in magnetic field intensity with distance from each source is non-monotonic. There are zones of minimum and maximum field intensity. This allows the zones of safe human presence and the location of protective magnetic screens to be clearly defined at the design stage. Criteria for taking into account the required number of spatial harmonics of the magnetic field have been determined. This indicator is determined by the relative distance from the field source to its dimensions in a spherical approximation.

Магнітні поля техногенного походження є чинником негативного впливу на людей. При наявності багатьох джерел магнітного поля їх сумарні значення непередбачувані. Закономірності поширення полів різнорідних джерел відрізняються. Це ускладнює процес планування розміщення електричного обладнання на визначених площах. Найбільш прийнятним способом прогнозування електромагнітної обстановки на стадіях проєктування є моделювання поширення магнітних полів багатьох джерел. Метою дослідження є моделювання поширення магнітних полів багатьох джерел з різними закономірностями їх просторових поширень. Результати дослідження. Найбільш вагомим чинником постійного впливу на людей є електромагнітні поля наднизької частоти. При цьому магнітна складова цих полів не екранується корпусами обладнання. Тому доцільно здійснити моделювання поширення магнітного поля. Показано, що усі джерела магнітного поля можна розглядати як комбінацію магнітних диполів. Для моделювання поширення магнітного поля дипольного типу використано співвідношення для векторного магнітного потенціалу. Моделювання поширення магнітних полів дипольно-квадрупольного типу доцільно застосувати рівняння Гауса для скалярного потенціалу. Це дозволяє враховувати наявність просторових гармонік магнітного поля. Здійснено моделювання поширення магнітного поля у площині перебування людей. Встановлено, що навіть за наявності суперпозиції полів зміна напруженості магнітного поля з відстанню від кожного джерела немонотонна. Існують зони мінімальної та максимальної напруженості поля.
Моделювання поширення магнітних полів множинних різнорідних джерел
Keywords: modelling; magnetic field; dipole; quadrupole; моделювання; магнітне поле; диполь; квадруполь